Piccoli mammiferi in ambienti agricoli: struttura delle comunità e relazioni con gli elementi del paesaggio rurale - Gentili S; Bonesi L; 2012; SIGURA, Maurizia (2012)
Agricultural landscapes are affected by continuous stresses that leads to changes in the structure and composition of the system. These stresses also affect the semi-natural elements of the rural landscape and the animal communities that live in them. In italy, there are several species of small terrestrial mammals that are adapted to agricultural environments, including Apodemus sylvaticus, A. agrarius, Microtus arvalis and A. flavicollis. The aim of this study is to investigate the role of these species as biological indicators of the level of stress in agricultural landscapes. For this purpose, we relate community and population parametrs of the species with landscape and habitat parameters along a gradient of decreasing quality and quantity of natural elements in the landscape. The study area is located in Friuli Venezia Giulia and incluses three different agricultural areas that represent three different levels of agricultural intensification in three different landscape types: hills, lowlands (low planin) and high plains. To study the populations of the four species mentioned above we used live trapping in three different landscape types, for a total of thirty sample sites. The sampling effort was of four trap-night per session and trapping sessions were carried out every three months. The preliminary results collected in the summer and autumn 2011 at the landscape scale demonstrate that indices of richness, diversity and equitability for the four studied species decrease with the decrease of structural heterogeneity and the increase of agricultural intensification. At the habitat scale the species prefer hedges (as habitat shelter) and meadows (increasing diversity and equitability), but we saw a different use of the corn field habitat between the different seasons, as in the summer we trapped individuals also in this habitat while in autumn this habitat was avoided. From these preliminery results it seems that the presence of the four rodent species, at the landscape scale, reflects the quality of the ...